Communicative functions of parents' child-directed speech across dyadic and triadic contexts. Issue 6 (9th November 2021) - NANDY, Angana; NIXON, Elizabeth; QUIGLEY, Jean
Abstract: This study examined the roles of parental gender and context in the communicative functions of parents' child-directed speech. Seventy three families with toddlers participated in the study. Dyadic and triadic parent-toddler interactions were videotaped during structured play activities. Results indicated context-dependent variability in parents' facilitative speech and gentle guidance. Parental gender effects were observed in parents' directive speech but no gender or contextual effects were observed in parents' referential speech. Results suggest the need for a closer examination of parental gender and contextual factors related to parents' speech functions.